PELATIHAN PERANGKAT DESA UNTUK MEWUJUDKAN GOOD VILLAGE GOVERNMENT BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (Jurnal AbdiMas Nusa Mandiri, 2026)
The Village Officials Training for the Realization of Good Village Governance Based on Information and Communication Technology (ICT) is part of a community service initiative aimed at enhancing the capacity of village officials to deliver efficient, transparent, and accountable public services. The program was implemented in Mekarbuana Village, Tegalwaru District, Karawang Regency, with participants consisting of village officials directly involved in administrative management and public service delivery. The community engagement employed a combination of methods, including structured training, hands-on mentoring, practical sessions on the use of the Village Information System (SID), and an evaluation of participants’ competencies through pre-test and post-test assessments. The training materials focused on improving digital literacy, managing administrative data using ICT tools, operating digital-based public service applications, and utilizing the official village website as a medium for transparency and public communication. The results demonstrated a significant improvement in participants’ technological competence and understanding. The average comprehension score increased from 58% to 87% after the training. Most participants were able to manage population and administrative data electronically, update public information content on the village website, and respond to citizens’ feedback through digital platforms. The program also fostered greater motivation among village officials to optimize ICT-based public services and to apply the principles of Good Village Governance. This activity proves that the integration of ICT into village governance not only improves efficiency and the quality of public services but also promotes community participation and builds a culture of transparency and accountability at the local government level.
Keywords: digitalization; digital literacy; digital village development service; information technology; village government